2005
DOI: 10.1021/ma050424j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polydispersity on the Formation of Vesicles from Amphiphilic Diblock Copolymers

Abstract: Using a continuous chain length distribution, the effect of polydispersity on the structures of vesicles self-assembled by amphiphilic polydisperse diblock copolymers in dilute solutions is investigated by two-dimensional (2D) real-space self-consistent-field theory. It is discovered that larger polydispersity favors the formation of smaller vesicles or quasi-vesicles. This polydispersity effect can be attributed to the segregation of copolymers according to their chain lengths. Two types of chain segregations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(108 citation statements)
references
References 40 publications
5
103
0
Order By: Relevance
“…83 When investigating the effects of polydispersity on the structure of diblock copolymer vesicles in dilute solution, it was found that larger polydispersity favors the formation of smaller vesicles. 84 This polydispersity effect was attributed to the segregation of copolymers according to their chain lengths to the inner and outer monolayers of the vesicle membrane, in good agreement with experimental results. Polydispersity was also found to affect the surface activity of triblock copolymers at the air-water interface.…”
Section: Self-consistent Field Theorysupporting
confidence: 85%
See 2 more Smart Citations
“…83 When investigating the effects of polydispersity on the structure of diblock copolymer vesicles in dilute solution, it was found that larger polydispersity favors the formation of smaller vesicles. 84 This polydispersity effect was attributed to the segregation of copolymers according to their chain lengths to the inner and outer monolayers of the vesicle membrane, in good agreement with experimental results. Polydispersity was also found to affect the surface activity of triblock copolymers at the air-water interface.…”
Section: Self-consistent Field Theorysupporting
confidence: 85%
“…Vesicle formation has also been observed from diblock copolymers in water with dynamic SCFT by the group of Doi. 70 Many SCFT studies have focused on the effects of polydispersity on various properties such as the cmc, 83 micellar size, 83,84 and vesicle stability. 84 The cmc was found to decrease by several orders of magnitude while the aggregation number increased when the polydispersity of pluronic polymers in water was increased.…”
Section: Self-consistent Field Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inter-polyelectrolyte complexes between polyacids and polybases appear to offer a versatile route for the preparation of asymmetric membranes through counter-ion complexation. [60] Theoretical studies suggest that segregation of block copolymers across the bilayer should be favoured for bimodal copolymer mixtures of differing molecular weights in order to stabilize the interfacial curvature [61,62] ( Figure 4). Subsequent experimental evidence for this segregation has been obtained using both AB diblock copolymer mixtures and ABC triblock copolymers.…”
Section: Block Copolymer Vesiclesmentioning
confidence: 99%
“…As far as blends of two block copolymers are concerned, few reports are available. Focus has been on AB/AB copolymers with different molecular weights 22,38 but less on AB/AC blends. AB/AC blends have been considered before, but only with similar molecular weights.…”
Section: Introductionmentioning
confidence: 99%